Hubungan Sumber Air Minum, Jamban Keluarga dan Saluran Pembuangan Air Limbah dengan Kejadian Diare di Kecamatan Pangkalan Kuras Kabupaten Pelalawan - Manek w; Suherman Sohor (STIKes Hang Tuah Pekanbaru, 2013)
Diarrhea is a bowel movement (defecation) by the number of stools more than usually (normal 100-200 ml per hour stool), with fecal liquid or semi-liquid (semi-solid), can also be accompanied by increased defecation. Based on data from the District Health Center Drain Base diarrheal disease is a disease with the highest order of 3 to Pangkalan Kuras people suffered in 2012 to 1645 events. This study aims to determine the relationship of drinking water treatment, the condition of latrines, and SaluranPembuangan Wastewater (SPAL) and the incidence of diarrhea in the community naturally Drain Base in 2013.This study is analitik kuantitatif with cross sectional design of the study, carried out at the Puskesmas Pangkalan Kuras with respondent households totaling 182 people. Data collection is by interview and observation with questionnaires, sampling techniques in this study is random sampling with sampling sytematic method. The results showed that the close relationship between the treatment of river water into drinking water (OR = 2.426), treatment of well water into drinking water (OR = 3.205), with the condition of the family latrine (OR = 3.755), and the condition of SPAL (OR = 3.588) and the incidence of diarrhea in Pangkalan Kuras. This result was obtained through chi-square analysis with 95% confidence level